ROI Estimation in a Scrum Project: A case study - Cortés Chavarría, Rita (2019)
Financial metrics are necessary to inform decisions about the beginning or continuity of a software development project to justify investments. This research discuses initial ROI (Return on Investment) estimates in a software project using Scrum and how to analyze variations in the initial calculations to make return on investment decisions during partial deliveries of the product. The case study included a survey, a review of documentation, two focus group sessions, and an exercise involving application of the proposed technique. Twenty-four professionals participated, of which 4 were Scrum trainers (17%), 4 were officials of the company where the estimation technique was applied (17%), and 16 were project managers of domestic and foreign software development companies (66%), all of whom had experience in project management. This study provides elements to be considered in future research on ROI calculation in projects using Scrum, and can be used as a guide to estimate and review financial metrics during the execution of an actual project.